Study of Reversible Nozzle Apparatuses Using Euler Methodology and CFD Technologies - Sazonov, Yuri A.; Mokhov, Mikhail A.; Bondarenko, Anton V.; Voronova, Victoria V.; Tumanyan, Khoren A.; Konyushkov, Egor I. (Civil Engineering Journal, 2024)
This research aims to study multiflow nozzle apparatuses designed to control the thrust vector within a full geometric sphere when the deflection angle of the thrust vector can vary in the range from +180 °to -180 °in any direction. The distribution of the working gas energy was considered as exemplified by a reversible nozzle apparatus with two outlet channels. It was shown that when using wedge-shaped diaphragms, the critical section area can be regulated while maintaining a constant pressure and flow rate of the working gas entering the inlet of the multiflow nozzle. In this case, the mass flow rate of the gas and jet thrust in each outlet channel change in direct proportion to the linear displacement of the diaphragm. Known conical diaphragms do not provide these results. To create promising control systems and train designers, it is proposed to use the Euler methodology and CFD technologies more widely based on the philosophy of technology. In the course of the numerical experiments, the options for the thrust cutoff (tailoff) were considered. A scientific basis has been prepared for solving problems with six degrees of freedom in three-dimensional space, considering Euler angles, when controlling the thrust vector within a full geometric sphere. Issues in flight trajectory planning (for example, for an unmanned aerial vehicle) are discussed with regard to new possibilities for extreme maneuvering. Two main areas for the development of scientific research are considered: energy-saving power generation and transportation systems (land, sea, and air). Doi: 10.28991/CEJ-2024-010-11-013 Full Text: PDF